Archaeal type IV pili and their involvement in biofilm formation - Pohlschroder, Mechthild; Esquivel, Rianne N. (Frontiers in Microbiology, 2015)
Type IV pili are ancient proteinaceous structures present on the cell surface of species in nearly all bacterial and archaeal phyla. These filaments are involved in a diverse array of critical cellular processes. While the core components of the pilus biosynthesis machinery are highly conserved, type IV pilins, the structural subunits of pili, share little sequence homology. However, the conserved structure of the signal peptides of these pilus subunits has allowed the development of prediction programs that accurately detect the processing sites recognized by bacterial and archaeal prepilin peptidases. Using these programs, the genomes of organisms from both prokaryotic domains have been shown to encode a diverse set of putative type IV pilins. Recently, in vivo studies in model archaea representing the euryarchaeal and crenarchaeal kingdoms confirmed that several of these pilins are incorporated into type IV adhesion pili. In addition to facilitating surface adhesion, these in vivo studies also showed that several predicted pilins are required for additional functions that are critical to biofilm formation. Examples include the subunits of Sulfolobus acidocaldarius Ups pili, which are induced by exposure to UV light and promote cell aggregation and conjugation, and a subset of the Haloferax volcanii adhesion pilins, which play a critical role in microcolony formation while other pilins inhibit this process. The recent discovery of novel pilin functions such as the ability of haloarchaeal adhesion pilins to regulate swimming motility rather than being unique to organisms that inhabit high salt environments may point to novel prokaryotic regulatory pathways. In this review, we will discuss recent advances in our understanding of the functional roles played by archaeal type IV adhesion pili and their subunits, with particular emphasis on their involvement in biofilm formation.